1988
DOI: 10.1177/154193128803200405
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Recognition Accuracy and Vocabulary Size of a Speech Recognition System on Task Performance and User Acceptance

Abstract: Industrial Engineering and Operations Research (ABSTRACT)Automatic speech recog n ition systems have at last advanced to the state that they are now a feasible alternative for human-machine communication in selected appli ...cations. As such, research efforts are now beginning to focus on characteristics of the human, the recognition device, and the interface which optimize the system performance, rather than the previous trend of determining factors affecting recognizer performance alone. This study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…15 Researchers usingan ASR-based data-retrieval task found that olderusers were slower to recover from systemrecognition errors. 16 Suchan effect illustrates the importance ofcarefully considering a user group's demography.…”
Section: ''You Havea Collect Call From (Caller's Name) Will You Accementioning
confidence: 99%
“…15 Researchers usingan ASR-based data-retrieval task found that olderusers were slower to recover from systemrecognition errors. 16 Suchan effect illustrates the importance ofcarefully considering a user group's demography.…”
Section: ''You Havea Collect Call From (Caller's Name) Will You Accementioning
confidence: 99%